Beyond the Click: A Deep Dive into Factors Influencing Digital Paylater - Kurniawati, Emaya; Suratman, Suratman; Widiastuti, C. Tri; Gusmao, Cristino (Integrated Journal of Business and Economics (IJBE), 2025)
This study explores key factors influencing Generation Z's intention to use digital pay-later services, focusing on perceived risk, ease of use, and financial technology (fintech) literacy. Specifically, it examines how perceptions of risk and ease of use affect usage intentions through the mediating role of fintech literacy. A quantitative research design and partial least squares (PLS) analysis were used to analyze survey data collected from Generation Z university students. The findings indicate that perceived ease of use significantly enhances intention to adopt digital pay-later services, whereas perceived risk demonstrates a more complex, indirect effect moderated by fintech literacy. Fintech literacy partially mediates the impact of both perceived risk and ease of use, highlighting the critical role of financial knowledge in fostering responsible digital pay-later adoption. These insights suggest that providers of digital pay-later services should focus on educational initiatives and design user-friendly products to meet the financial literacy needs of Generation Z consumers.